Effects of Different Periodization Models in Strength Training on Physical and Motor Skills during 24 Weeks of Training - Déborah de Araújo Farias; Michel Moraes Gonçalves; Sérgio Eduardo Nassar; Euzébio de Oliveira (Brazilian Army, 2021)
Introduction: Periodization is the accurate manipulation of methodological variables of strength training (ST) to provide a progressive increase in the different manifestations of muscle strength. The most used models in ST are linear and undulatory periodization. Objective: Evaluate the effects of 24 weeks of training by applying three different models of ST periodization: Linear Periodization (LP), Weekly Undulating Periodization (WUP) and Daily Undulating Periodization (DUP) on: upper limb (UL) strength (submaximal and endurance), submaximal strength and power of the lower limbs (LL) and on other components of physical fitness (flexibility, agility and abdominal endurance strength). Methods: Experimental, longitudinal study, with a convenience sample, in which 29 people of both sexes participated, randomly allocated to the groups. Tests were performed pre- and post-intervention. ANOVA (two-way) of repeated measures was performed. Results: There was a significant increase in submaximal strength of the UL in the three periodization models: LP (p<0.001), the WUP (p=0.002) and DUP (p=0.001). There was also a significant increase in submaximal strength of the LL with LP (p=0.002), WUP (p<0.001) and with DUP (p=0.001). No significant intergroup differences were found in any test and time. Conclusion: In individuals without training experience, 24 weeks of TF provided gains in different manifestations of strength, regardless of the periodization model (LP, WUP or DUP). PL and WUP seem to be better at providing LL power gains in the horizontal jump.